Effects of Temperature on the Microbial Growth and Quality of Unsealed Dry Pet Food during Storage - Dongbin, P.; Hyun Jung, L.; Sethukali, A.; Dong-Gyun, Y.; Sungkwon, P.; Cheorun, J. (Korean Society of Animal Science and Technology, 2024)
Dry pet food is a convenient option for pet owners, but its storage conditions can impact its microbial growth and quality. In this study, we examined the effects of storage temperature on the quality and microbial growth of dry pet food. The pet food was stored at 25°C and 35°C, respectively, and samples were analyzed on days 0, 30, 90, and 120 for microbial growth and quality attributes such as pH, color, lipid oxidation, and volatile basic nitrogen. While no initial microbial growth was observed due to the low water content and water activity, quality attributes showed changes over time. However, the changes were negligible, indicating that dry pet food remains feedable for up to 120 days even at a storage temperature of 35°C. These findings suggest that dry pet food can be safely stored at room temperature or up to 35°C without compromising its quality.
Keywords: Dry pet food; Storage temperature; Microbial growth; Quality